SAT0365 Risk Factors for Visual Loss in Giant Cell Arteritis (GCA). (15th July 2016) - Solans-Laqué, R.; Fraile, G.; Escalante, B.; Fonseca, E.; Martinez-Zapico, A.; Perez-Conesa, M.; Abdilla, M.; Montegaudo, M.; Caminal, L.; Gracia, B.; Del Castillo, M.J.; Fanlo, P.; et al.
Abstract : Background: visual loss is the most frequent ischemic complication and the main cause of permanent disability among patients with GCA. To identify factors related to this complication may help physicians to start an early treatment and assay new therapies Objectives: To analyse clinical and histological findings related to visual loss in patients with GCA Methods: demographic, clinical and histological features of patients with biopsy-proven GCA recruited at 10 Hospitals from Spain (REVAS Study) were analysed. Statistical analysis was performed using SPSS vs. 20 Results: 418 patients were included: 290 (69.4%) females (ratio F/M: 2.3/1). The mean age at diagnosis was 75.5 ± 7 (53–92), 55% patients being older than 75y. The median diagnosis delay was 7 weeks (IQR 4–12). Cardiovascular risk factors were present in 45% of patients (hypertension in 48.8%, hypercholesterolemia in 26.6%, diabetes mellitus in 19.4%). The most frequent symptoms at CGA diagnosis were recent onset headache (81%), constitutional symptoms (47%) and polymyalgia rheumatic (44.5%). Jaw claudication, cranial hyperesthesia and amaurosis fugax were reported by 44.5%, 31.8% and 16.5%2 of patients, respectively. A total of 84 patients suffered vision loss (in 4 cases involving both eyes), due to anterior optic ischemic neuropathy (AION) in 78 (92.8%), and to central retinal artery occlusion in 6 (7.1%). CVA was recorded in 6.5% of cases. Anemia was present in 76.3% of patients. Mean ESR was 98±23.4. Patients with visual loss presented more frequently jaw claudication (71.6% vs 39.2%), cranial hyperesthesia (52.6% vs 28.7%) and amaurosis fugax (52.6% vs 8.6%), and less frequently low-grade fever (16.7% vs 43.1%) and toxic syndrome (37.2% vs 53.4%). Regarding to histological findings: patients with visual loss presented on TAB more intimal hyperplasia (70.5% vs 57.7%) and lumen occlusion >50% (53.8 vs 19.4%). No other differences were found. Univariated analysis showed than AION was significantly related to the presence of amaurosis fugax (OR 12.8, 95% CI 7.0–23.3, p<0.001), jaw claudication (OR 4, 95%CI 2.3–7.1, p<0.001), cranial hyperesthesia (OR 2.4, 95%CI 1.5–4), and age at diagnosis ≥75 years old (OR 2.7, 95% CI 1.5–4.6, p<0.001). An inverse relationship between AION and the presence of low-grade fever and toxic syndrome was found. No significant relationship was found between visual loss development and cardiovascular risk factors or CVA Conclusions: AION is the most frequent cause of vision loss in GCA. Jaw claudication, cranial hyperesthesia, amaurosis fugax, and age >75 older at diagnosis are significantly related to AION. A wider recognition of the disease would potentially reduce the prevalence of irreversible visual loss among GCA patients. Disclosure of Interest: None declared